2021
DOI: 10.51507/j.jams.2021.14.4.137
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability and Psychometric Analysis in Patients with Hyperactive Heart Fire Syndrome

Abstract: Background: Hyperactive heart fire syndrome is characterized by anxiety, insomnia, dream-disturbed sleep, tongue ulcers, heat in the hands, and palpitations. However, syndrome differentiation is often subjective due to a lack of objective, quantifiable variables. Objectives: To identify changes in heart rate variability (HRV) and psychometric analysis in patients with hyperactive heart fire syndrome. Methods: Healthy controls (n = 33) were compared to patients with hyperactive heart fire syndrome (n = 48) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…We found larger values of pNN50 and HF (nu) in the frail older adults with respect to the other populations. A higher HF (nu) is often interpreted as an increased parasympathetic modulation which is usually beneficial for health [ 42 ]. A counter example is presented by Kabbach et al [ 43 ], who reported a higher HF in acute exacerbated patients with chronic obstructive pulmonary disease (COPD), compared to stabilized patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found larger values of pNN50 and HF (nu) in the frail older adults with respect to the other populations. A higher HF (nu) is often interpreted as an increased parasympathetic modulation which is usually beneficial for health [ 42 ]. A counter example is presented by Kabbach et al [ 43 ], who reported a higher HF in acute exacerbated patients with chronic obstructive pulmonary disease (COPD), compared to stabilized patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a higher breathing rate (EDR) in frail older adults than in non-frail older adults. Therefore, we suggest that the higher HF (nu) in frail older adults could be due to an increased breathing rate rather than an increased parasympathetic modulation [ 42 ]. We cannot interpret the dominance or absence of sympathetic modulation based on the LF components as it has been found that LF incorporates information of the two modulations, both sympathetic and parasympathetic [ 44 ], therefore, to understand specifically the alterations of the sympathetic modulation in frail older adults, a different experimental protocol should be carried out.…”
Section: Discussionmentioning
confidence: 99%